Equilibrium Locations of Vertically Linked Industries. - Venables, A (CEPR, 1993)
This paper considers the locational choice of firms in an upstream and a downstream industry. Both industries are imperfectly competitive, with firms subject to increasing returns. There are transport costs between the two locations. Depending on the level of these costs there may be a single equilibrium with production diversified between locations, or multiple equilibria, some of which involve agglomeration at a single location. Typically the forces for agglomeration are greatest at intermediate levels of transport costs. Reducing these costs from a high to an intermediate level will cause agglomeration and consequent divergence of economic structure and income levels; reducing them to a low level may cause the industries to operate in both locations, bringing convergence of structure and income.